(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The 20th century histories writtenby the British and Indian historians on early Turkish rule help us to knowabout the state of affairs during the 13th century. They enrich our knowledgeof the socio-political, economic and cultural milieu present at those times.The histories written by British and Indian historians had different set ofobjectives and different aims. But, constant improvements and new beginnings inthe field of historiography helped its cause. However no work has beenpublished till date on the 20th century historiography of Indian and British historianson the early Turkish Rule in northern India. The present investigation is ahumble attempt in this direction. This work is divided into six chapters withan introduction at the beginning and conclusion at the end. It is an Endeavourto trace the characteristics and developments in the field of historiographyduring 20th century and makes an assessment of the historical writings onpolity, society, economy, religion and institutions of early Turkish rule. Anassessment of these writings initiated new insights and supplements theKnowledge already diffused through the writings of 20th centuryHistorian. A movement towards the study of the religious and cultural historyof the peoples of the sub-continent during the early Muslim period wasperceptible both in periodical literature appearing in English and alsooccasionally in monographs. Once again, it cannot be said that Britishhistorians have taken any prominent place in this shift of attention. Not muchwork had been done on the religious aspects of the early Turkish rule history.